Pemberdayaan Masyarakat Dengan Pengabdian KKN Di Desa Libunio Kecamatan Soa Kabupaten Ngada - Gado, Alfridus; Aburman, Bernadinus; Tan, Valentinus (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
The implementation of the Flores University KKN in 2023 will be carried out collectively, namely on 01-31 August 2023 with the theme "Community Empowerment for Shared Welfare". KKN aims to increase students' empathy and concern for the community, being able to work together in groups, being responsible, disciplined, and having a work ethic. The location of the KKN activity is in Libunio Village, Soa District, Ngada Regency, East Nusa Tenggara Province. This KKN activity is the result of collaboration between the local village government, community, students, and Field Supervisors (DPL). The aim of this activity is so that students can apply what they have learned in college, and gain learning experience by being directly involved with the community, through the problems they find and finding solutions. There are several problems encountered at the location, so there needs to be a joint effort to reduce or overcome these problems. 1) Due to drought and lack of clean water, a water storage tank was made for the Libunio village community, 2) a village road to facilitate access for the Libunio village community, 3) held joint devotional work activities every Saturday to make it look clean and comfortable, 4) made a planting monument KB village to support the KB program, 5) planting trees with the Soa police chief for greening, 6) making RT signs to indicate the RT in each hamlet so that it looks attractive and 7) making gates to celebrate the 78th anniversary of the Republic of Indonesia. It is hoped that the results of this activity will provide benefits to the government and local community, and can work together for next year's KKN activities.